2015
DOI: 10.1590/1983-21252015v28n321rc
|View full text |Cite
|
Sign up to set email alerts
|

Morfogênese Da Palma Forrageira Irrigada Por Gotejamento

Abstract: RESUMO: Objetivou-se avaliar a evolução do crescimento de clones de palma forrageira submetidos a diferentes condições de disponibilidade de água no Semiárido brasileiro durante um ano de anomalia climática (biênio 2012-2013). O experimento foi conduzido no primeiro ano produtivo do segundo ciclo da cultura (março de 2012 a fevereiro de 2013) no município de Serra Talhada (PE). O delineamento experimental foi em esquema fatorial 3x3 com três repetições, sendo utilizados três intervalos de aplicação de uma lâmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 11 publications
4
34
0
18
Order By: Relevance
“…Assessing the morphogenesis of varieties of dripirrigated fodder forage cactus, cv. Miúda, IPASertânia and Orelha de Elefante Mexicana, Pereira et al (2015) reported a mean height of 48.8 cm after 12 months of growth.…”
Section: Resultsmentioning
confidence: 99%
“…Assessing the morphogenesis of varieties of dripirrigated fodder forage cactus, cv. Miúda, IPASertânia and Orelha de Elefante Mexicana, Pereira et al (2015) reported a mean height of 48.8 cm after 12 months of growth.…”
Section: Resultsmentioning
confidence: 99%
“…Neste estudo foi avaliada a superação da dormência em sementes das espécies: Angico (A. colubrina), Jurema-branca (P. (Alvares et al, 2013;Pereira et al, 2015). A temperatura e a umidade atmosférica, durante as duas épocas distintas, foram monitoradas através de uma estação meteorológica automática, localizada a cerca de 300 m da área experimental e pertencente ao Instituto Nacional de Meteorologia-INMET (INMET, 2017).…”
Section: Methodsunclassified
“…The Northeastern region of Brazil presents a large space-time variation in the climate and in the weather, in intra and interannual scale, being 56.46% of its territory represented by the semiarid region . The Brazilian semiarid region (BSA) is characterized by large periods of water scarcity, mainly due to irregularity and poor rainfall distribution (i.e., 350 to 800 mm year -1 ), with potential evapotranspiration (ETp) values of up to 2,000 mm year -1 , with a wide variation in the air temperature (20.1 to 32.9 ºC) and relative humidity of 60% Pereira et al, 2015). According to Alves et al (2014a) and Carneiro et al (2014), these conditions are related to the high incidence of solar radiation in this region, also affecting soil temperature and evapotranspiration, affecting plant growth and development.…”
Section: Literature Review Characterization Of the Environmentmentioning
confidence: 99%
“…Forage cactus is a xerophyte species that due to its morphological and physiological characteristics it presents significant tolerance to environments with extended periods of drought. Even with these characteristics, studies have shown the successful performance of this cactus in response to the use of irrigation, with which it is possible to improve the development and productivity of this cultivation (Almeida et al, 2011;Pereira et al, 2015;Queiroz et al, 2016;Silva et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%